2016
DOI: 10.1007/s00428-016-2035-5
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of measurement of myometrial invasion in endometrial carcinoma

Abstract: Myometrial invasion (MI) as a percentage (%MI), categorized into <50 or ≥50 %, is an important predictor of prognosis in endometrial carcinoma. Recent studies suggest that tumor-free distance (TFD) to serosa and the absolute depth of invasion (DOI) might be stronger predictors of prognosis. Although reproducibility is important in clinical practice for patient prognostication and treatment, reproducibility of these methods for the measurement of MI is largely unknown. One or two slides from 50 patients with FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…With this study, we add to previous studies regarding reproducibility of pathological reporting of other EC specific characteristics such as histological typing, tumour grading, assessment of cervical involvement and assessment of myometrial invasion. [32][33][34][35] Levels of reproducibility of these tumour characteristics are similar to our results for LVSI assessment. None of the previous studies specifically focused on LVSI assessment, but there are two studies that report on reproducibility of LVSI in EC.…”
Section: Discussionsupporting
confidence: 86%
“…With this study, we add to previous studies regarding reproducibility of pathological reporting of other EC specific characteristics such as histological typing, tumour grading, assessment of cervical involvement and assessment of myometrial invasion. [32][33][34][35] Levels of reproducibility of these tumour characteristics are similar to our results for LVSI assessment. None of the previous studies specifically focused on LVSI assessment, but there are two studies that report on reproducibility of LVSI in EC.…”
Section: Discussionsupporting
confidence: 86%
“…Chattopadhyay et al (10) demonstrated that TFD is an independent predictor of disease specific survival, recurrence and pelvic lymph node involvement. Data regarding the cut-off value of TFD in patients with endometrial cancer which revealed the best predictive performance value varied between 1,75 and 10 mm (7,14). In the current study, only >50% MI was found to have a predictive value for cervical involvement, type 2 and LVSI.…”
Section: Discussionmentioning
confidence: 43%
“…To our knowledge, this is the first study demonstrating the superiority of MI compared to TFD and DMI in predicting EC outcomes. This can be explained by the reduced number of patients included in this study compared with other study (11,14). Besides, the lack of equitable distribution of histological types with a large predominance of endometroid carcinoma seems to influence the results of the study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As FIGO stage I disease is the most frequently seen endometrial cancer [5], myometrial invasion depth is one of the most important indicators that clinicians and pathologists investigate. Although there are many studies assessing the importance of myometrial invasion (MI) using a cut-off limit as 50% of MI [6][7][8][9], there are limited number of studies evaluating tumor-free distance (TFD) to the serosa [5,10,11]. Moreover, most of them evaluated TFD for prediction for lymph node metastasis but the long-term follow-up is taken into consideration in only few studies [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%